“Windows of Opportunities” of Small and Medium Business for Implementation of New Industrial Policy - V. P. Bauer; E. S. Ageeva (Мир новой экономики, 2018)
Relevance of the work due to the need to find opportunities to practice implementation of industrial policy, formulated in the new federal law. The subject of research is the Russian small and medium business (MSB). The aim of the article is to identify the composition of functions and mechanisms for MSB needed to implement the above policy. To achieve the goal proposed to use the model of the “window of opportunity” Overton, which for the “window of opportunity” for MSB to use the enlarged economic space levels of the hierarchy. This approach allows a new level of quality to give advice on the use of the capacity of MSB to enable them to participate in meeting the challenges of the new industrial policy. It is concluded that this approach allows a new level of quality to identify the potential for MSB to enable them to participate effectively in the implementation of the new industrial policy.